OVERCOMING CHALLENGES IN COVID-19 PANDEMIC : A PERSPECTIVE IN ADAPTATION OF THE COMMUNITY MENTAL HEALTH SERVICE IN A TEACHING HOSPITAL - Nur Iwana, Abdul Taib; Marhani, Midin; Tuti Iryani, Mohd Daud (2021)
During the current COVID-19 pandemic, Malaysia had implemented a lockdown via Movement Control Order (MCO) nationwide, beginning from 18 March 2020 until present. The restrictions affected health services including community mental health services as there were no clear response guidelines yet available for it. We aim to share our experience in adapting services at a teaching hospital setting to the changes during MCO. Our goals were to minimize cross infection between clients and staff while maximizing service delivery to ensure clients’ continuation of care. We identified limitations and potentially sustainable improvements to direct further service development. The main community mental health services of Hospital Canselor Tuanku Muhriz (HCTM) consists of assertive home care and psychosocial rehabilitation programs for the severely mentally ills. Modifications in assertive care include regular risk stratification of patient’s symptoms and COVID-19 risks, phone consultations, drive-thru injection services, mobilizing other available resources such as family members or nearby clinics and practicing strict home visit standard operating procedures. Psychosocial rehabilitation services such as social skills training, supported employment, family intervention and peer support groups were modified by means of teleconsultations using video calls and instant messaging services for a continuous therapeutic efforts. These modifications were practiced for the past one year and were adjusted accordingly over time to accommodate the changing MCO restrictions. There had been no recorded positive cases among staff and clients with no increase rates of relapse among the clients during this period. Clients also reacted positively with the modifications. The innovative modifications in ensuring continuing service delivery while preserving safety in this centre can act as a guide to improvise healthcare deliveries during a pandemic.